2007
DOI: 10.1021/jo701942e
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of Highly Substituted Isoxazoles by Electrophilic Cyclization:  An Efficient Synthesis of Valdecoxib

Abstract: A large number of functionally-substituted 2-alkyn-1-one O-methyl oximes have been cyclized under mild reaction conditions in the presence of ICl to give the corresponding 4-iodoisoxazoles in moderate to excellent yields. The resulting 4-iodoisoxazoles undergo various palladium-catalyzed reactions to yield 3,4,5-trisubstituted isoxazoles, including valdecoxib.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
87
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(91 citation statements)
references
References 55 publications
4
87
0
Order By: Relevance
“…So always using SDS as surfactant, we further conducted the experiments of the carbonylative coupling of ferrocenylethyne with various aryl iodides at room temperature under a balloon pressure of carbon monoxide for 6 h. The results were listed in the following Table 2. According to Table 2, we found that most of the reactions produce moderate to excellent yields of carbonylative coupling products (entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It seems that the substituted iodides having electron-donating group (entries 1-2, 4-6, 8,11) give better yields than those having electron-withdrawing group (entries 10, [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So always using SDS as surfactant, we further conducted the experiments of the carbonylative coupling of ferrocenylethyne with various aryl iodides at room temperature under a balloon pressure of carbon monoxide for 6 h. The results were listed in the following Table 2. According to Table 2, we found that most of the reactions produce moderate to excellent yields of carbonylative coupling products (entries [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It seems that the substituted iodides having electron-donating group (entries 1-2, 4-6, 8,11) give better yields than those having electron-withdrawing group (entries 10, [15][16][17][18].…”
Section: Resultsmentioning
confidence: 99%
“…1 Introduction a, b-Alkynyl ketones have attracted considerable interest as useful intermediates for the synthesis of some biologically active molecules [1] and heterocyclic derivatives [2][3][4], such as pyrroles [5], furans [6,7], furanones [8], triazoles [9], pyrazoles [10], 3,4,5-trisubstituted isoxazoles [11], indolizidinones [12], pyridinones [13], and quinolines [14]. They have also been used in the synthesis of natural products [15], such as chiral propargylic alcohols [16], conjugated dienones [17] and so on.…”
mentioning
confidence: 99%
“…After a few minutes (5)(6)(7)(8)(9)(10), the solution was brought to 0°C in an ice bath and 4-chlorobenzene sulfonamide (ArCl) (0.01 mol, 1.92 g) was added under vigorous stirring. The reaction mixture was checked by thin layer chromatography.…”
Section: Synthesis Of 4-[5-chlorophenylamino)-134-thiadiazole-2-yl-mentioning
confidence: 99%
“…They have been known as the proposed inseparable intermediates in a number of cycloisomerization reactions of o-alkynylbenzaldehydes in the presence of metal catalyst or promoters [9][10][11][12][13][14][15][16][17][18][19][20][21] or other electrophiles [22][23][24][25][26][27], until the recent isolation and characterizations of stable isochromenylium salts were achieved by our group [28]. These air-and moisture-stable isochromenylium tetrafluoroborates could be conveniently prepared by direct treatment of the o-alkynylbenzaldehyde precursors with HBF 4 in acetic acid.…”
Section: Introductionmentioning
confidence: 99%